1991
DOI: 10.1051/jp4:1991321
|View full text |Cite
|
Sign up to set email alerts
|

Strain Correlation at Different Structural Levels for Dynamically Loaded Hollow Copper Cylinders

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The experimental procedures were originally developed for metals but were modified for granular and brittle materials. 12,[20][21][22][23][24] This method consists of two explosive events: the first event to fracture the ceramic and the second event to deform the fragmented ceramic.…”
Section: B High-strain-rate Experimentsmentioning
confidence: 99%
“…The experimental procedures were originally developed for metals but were modified for granular and brittle materials. 12,[20][21][22][23][24] This method consists of two explosive events: the first event to fracture the ceramic and the second event to deform the fragmented ceramic.…”
Section: B High-strain-rate Experimentsmentioning
confidence: 99%
“…In a recent paper, an experimental technique, called the 'thick-walled cylinder (TWC) method', has been used by Nesterenko et al [1] and Bondar and Nesterenko [2] to study strain localization at high strain rates. The strain rate in the TWC method can be much higher than the strain rate that can be achieved by conventional methods, such as the Hopkinson bar technique.…”
Section: Introductionmentioning
confidence: 99%
“…The collapsing thick-walled cylinder technique was shown to produce controlled and repeatable helical shear band patterns, which allowed to investigate -for the first time-the collective behavior and spacing of shear bands at strain rates of ≈ 10 4 s −1 . Experiments performed with Copper, AISI 304L, pure Titanium, Ti6Al4V and Tantalum specimens provided indications of the actual sensitivity of these materials to shear banding, and revealed that the critical strain leading to shear bands formation and the average separation between shear bands varies from material to material (Bondar and Nesterenko, 1991;Nesterenko and Bondar, 1994;Nesterenko et al, 1995Nesterenko et al, , 1997Nesterenko et al, , 1998Xue et al, 2002Xue et al, , 2004. Similar conclusions were obtained from the recent experiments performed by Yang et al (2011), Yang andJiang (2016) and Yang et al (2017) with different tempers of Ti-1300 titanium alloy and ZK60 magnesium alloy, which showed that the distribution, width, and spacing of the adiabatic shear bands varies with the heat treatment applied to the specimen before testing.…”
Section: Introductionmentioning
confidence: 99%